Cognitive Impairment in Patients with Chronic Kidney Disease: A Literature Review - Srikongmark, Piyawat; Vongsanim, Surachet (Journal of the Nephrology Society of Thailand, 2025)
Cognitive impairment is increasingly recognized in patients with chronic kidney disease (CKD), including those on kidney replacement therapy. Cognitive impairment is associated with a higher risk of hospitalization, dialysis withdrawal, and death. Understanding and early detection of this condition should attenuate these complications. CKD patients have more risk factors for developing cognitive impairment including traditional risk factors, CKD-related risk factors, and dialysis-related risk factors. These will affect through vascular dysfunction, impaired cerebral adaptation, chronic inflammation, and uremic toxins accumulation. Currently, effective therapy for cognitive impairment in CKD patients is somewhat limited. Therefore, understanding the mechanisms and avoiding the risk factors are the principal management to decrease the upcoming cognitive impairment.